The Incidence Of Anemia In Teenagers Viewed From Habits Of Consuming Areca Nut In The Working Area Of The Ulilin Community Health Center, Merauke Regency, South Papua Province. - Ami Fitrianni; Putri Eka Sejati; Nining Istighosah; Teti Repursari (Journal of Health Science Community, 2024)
In Indonesia, the habit of chewing areca nut is a habit carried out by various tribes, including the Papuan tribe. Papuan people chew areca nut to flavor their mouths. Then it continues to be enjoyable and feels good so it is difficult to let go. This study aims to determine the incidence of anemia in adolescents viewed from the habit of consuming areca nut in the working area of ​​the Ulilin Community Health Center, Merauke Regency, South Papua Province. This research uses a research design Observational Analytics with approach cross sectional. With technique purposive sampling A sample of 35 respondents was obtained, the independent variable was the habit of consuming areca nut and the dependent variable was the incidence of anema. Statistical tests are used Chi-Square to find out the relationship between the two variables. The results of research from 35 respondents showed that most of the respondents had criteria for the incidence of anemia Most of them suffer from anemia as many as 23 respondents (65.7%) and most of the young women often consume areca nut as many as 24 respondents (68.6%). Analysis uses statistical tests Chi-Square results were obtained p = 0.013 < 0.05, then H0 is rejected and H1 is accepted, which means there is a relationship between the incidence of anemia and the habit of teenagers consuming areca nuts in the working area of ​​the Ulilin Community Health Center. It is hoped that the local community, especially young women, can gain knowledge regarding the negative impacts of the habit of consuming areca nut and it is hoped that women of childbearing age can pay attention to the nutritional status (protein and iron) that the body needs in an effort to reduce the risk of developing anemia.